Relationship Between Sleep–Wake Disturbance and Risk of Malnutrition in Hospitalized Patients With Cirrhosis - Hui, Yangyang; Wang, Xiaoyu; Yu, Zihan; Feng, Hongjuan; Li, Chaoqun; Mao, Lihong; Fan, Xiaofei; Lin, Lin; Cui, Binxin; Chen, Xin; Sun, Longhao; Wang, Bangmao; et al. (Frontiers in Nutrition, 2021)
Both sleep–wake disturbance and malnutrition are common in cirrhosis and might be associated with similar adverse outcomes, such as impaired health-related quality of life, hepatic encephalopathy, and sarcopenia, but there is no study investigating the relationship between these two. We aimed to explore the relationship between sleep–wake disturbance [estimated by the Pittsburgh Sleep Quality Index (PSQI)] and malnutrition risk [estimated by the Royal Free Hospital-Nutritional Prioritizing Tool (RFH-NPT)]. About 150 patients with cirrhosis were prospectively recruited. The nutritional risk is classified as low (0 points), moderate (1 point), and high (2–7 points) according to the RFH-NPT score. A global PSQI >5 indicated poor sleepers. Furthermore, multivariate linear regression analyses were performed to determine the relationship between sleep–wake disturbance and malnutrition. The median PSQI was seven, and RFH-NPT was two in the entire cohort, with 60.67 and 56.67% rated as poor sleep quality and high malnutrition risk, respectively. Patients with cirrhosis with poor sleep quality had significantly higher RFH-NPT score (3 vs. 1, P = 0.007). Our multivariate analyses indicated that male patients (β = 0.279, P < 0.001), ascites (β = 0.210, P = 0.016), and PSQI (β = 0.262, P = 0.001) were independent predictors of malnutrition. In addition, the differences regarding PSQI score were more significant in male patients, as well as those >65 years or with Child-Turcotte-Pugh class A/B (CTP-A/B) or the median model for end-stage liver disease (MELD) <15. Taken together, the sleep–wake disturbance is strongly correlated with high malnutrition risk in patients with cirrhosis. Given sleep–wake disturbance is remediable, it is tempting to incorporate therapies to reverse poor sleep quality for improving nutritional status in patients with cirrhosis.